Pengaruh Leverage terhadap Return Saham di Bursa Efek Indonesia Periode 2008-2017 dengan Variabel Moderasi Indeks Saham Lq45 - Nurhayatunisa, Nurhayatunisa; Kesuma, Ali (Universitas Darwan Ali, 2020)
The purpose of this research is to determine the effect of leverage on stock returns and to find out whether the LQ45 index moderates the negative influence of leverage on stock returns. The sampling technique is purposive sampling. The sample size is 2210 which consists of 221 companies from all sectors except finance for 10 years from 2008-2017. The estimation of the research model uses panel regression. The results of this study indicate that leverage has a positive effect on stock returns and the effect of leverage on stock returns is no difference between stocks that are within the LQ45 index and those that are not included in the LQ45 stock index.